Analisis kelayakan bisnis: Meliora pictures sebagai industri jasa fotografi - Windiasari, Fica Afria; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
Meliora Pictures is a photography service business based in Malang, targeting mainly students. Despite facing intense competition, the business has great potential to grow by leveraging its strategic location and demand for documentation of important moments. Marketing strategies, such as word-of-mouth and social media, can be enhanced by optimizing digital marketing, diversifying services, and focusing on service quality to increase customer loyalty. This study provides recommendations to improve branding, operational efficiency, and more targeted marketing strategies.